Versatile roles of organelle outer membranes in intracellular communication - Kentaro Inoue (Frontiers Research Topics, 2015)
This topic covers emerging knowledge about the properties and functions of the outer membranes of chloroplasts and mitochondria. These outer membranes house various processes necessary for efficient communication and thus integration of the organelles with and into their surroundings in the cytoplasm. Such processes include, but are not limited to, protein import, organelle division, organelle movement, metabolism, and metabolite/ion transport. Recent molecular genetic, biochemical and cell biological studies have revealed functions of various outer membrane proteins. These findings have helped address and generate diverse biological and evolutionary questions at molecular, cellular and whole organism levels. The topic should encourage contributions of scientists from various disciplines and thus would provide the field with opportunities to "think outside the box" and to develop potential collaborations. The topic is also aimed to stimulate interests of general audience in the outer membranes of chloroplasts and mitochondria.